(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Sadova V. V. Process aspects concerning formation of students’ history-and- pedagogy culture. The article deals with some theoretical foundations of students’ history-and-pedagogy culture as an education-and-personality phenomenon; on the basis of science literature analysis the explication of the «history-and-pedagogy culture» term is presented; the process aspects concerning the formation of students’ history-and-pedagogy culture in the educational field of philology faculties are detailed.